Experimental and Kinetic Studies on Adsorption of Trace Amount of Nickel from aqueous solutions using a new chelating Adsorbent Polystyrene (4-azo-1')-2'-hydroxy-5'-sulfobenzene - Alwesabi, Ali Saad; Alabsi, Badr Ismael (Eurasian Journal of Analytical Chemistry, 2019)
The modern instrumental analysis methods do not always allow direct determination of trace amounts of elements due to influence of the matrix composition of the sample. A novel polystyrene (4-azo-1')-2'-hydroxy-5'- sulfobenzene abbreviated as PSAHSB adsorbent synthesized based on amino polystyrene functionalized with chelating azo phenolic groups was applied for removal of trace Ni (II) ions from aqueous solutions under batch conditions. The parameters including pH, temperature and contact time on removal of nickel ions were studied extensively. The ionization constants of an adsorbent were investigated. The adsorption isotherm, thermodynamics and kinetics parameters were also investigated. To gain insight into the adsorption kinetics, both the pseudo-kinetics were examined. The adsorption of trace nickel ions increased smoothly in the pH range of 1-3, then remained at a higher level for the pH range of 3-7.5, but decreased sharply at pH large than 8, which demonstrated that the adsorption was affected strongly by pH. On the other hand, the adsorption capacity was increased sharply with the temperature rising. The adsorption equilibrium time could be reached in 25min. The equilibrium data could fit the Langmuir isothermal model very well, and the thermodynamic analysis suggested that the adsorption of nickel ions on the adsorbent is a spontaneous and endothermic process. The results indicated the pseudo-second-order kinetic model fitted the experimental data better. The adsorbent have three ionization constants and exhibits excellent stability and high regeneration. The absorbent can be used efficiently for treatment of Ni+2ions from naturally- occurring and industrial materials.